DEVELOPMENT OF THE COMPOSITION AND TECHNOLOGY OF COATED TABLETS WITH RHEUM CORDATUM LOSINSK. EXTRACT - G.T. ZHUMASHOVA; Z.B. SAKIPOVA (Avicenna Tajik State Medical University, 2020)
Objective: Development of a rational composition, optimal technology, standardization criteria for tablets with Rheum cordatum extract, establishing the stability of the composition and storage conditions. Methods: As an active pharmaceutical substance, a standardized extract of Rheum cordatum was used. Pharmacopoeial excipients for the production of tablet mass are magnesium hydroxycarbonate, croscarmellose sodium, microcrystalline cellulose, Plasdone S-630, magnesium aluminum metasilicate, calcium stearate, purified water and film coating Opadry 85F18422 White. To obtain tablets qualified equipment was used in the technological process: a tablet mass mixer, a rotary tablet press, highly efficient film coating equipment, a packaging machine / blister machine. When developing the tablets, we were guided by the «Quality by design» concept of medicines, based on ICH guidelines: ICH Q11 «Development and manufacture of medicinal substances», ICH Q8 «Pharmaceutical Development» and ICH Q10 «Pharmaceutical Quality System». Standard pharmacopoeial research methods were used. Results: 50 experimental mass models for tableting have been developed in the variants of combining excipients and active substance in an effective single dose of 300 mg. Only 4 models of the core tablets obtained met the selection criteria (abrasion, crush resistance, disintegration, and dissolution). The optimal tableting method using wet granulation is substantiated, which makes it possible to obtain tablets of the proper pharmacopoeial quality and the following composition: soft rhubarb root extract, magnesium hydroxycarbonate, croscarmellose sodium, microcrystalline cellulose 102, Plasdone S-630, magnesium aluminum metasilicate, calcium stearate. To coat the obtained tablet cores, the following film coating composition was selected: Opadry 85F18422 White, consisting of polyvinyl alcohol, titanium dioxide E 171, macrogol 4000 and talc. Conclusion: The pharmaceutical development of coated tablets with an extract of Rheum cordatum has been done. The rational composition and optimal technology for producing tablet cores coated with a film coating of Opadry 85F18422 White were established. The quality of the obtained tablets was evaluated, the stability of the composition for 9 months was studied, the results of quality indicators are within acceptable standards, and research in this direction is going on.